Childhood trauma and coping in patients with psychotic disorders and obsessive-compulsive symptoms and in un-affected siblings. (January 2020) - ,; Alizadeh, Behrooz Z.; van Amelsvoort, Therese; Bartels-Velthuis, Agna A.; van Beveren, Nico J.; Bruggeman, Richard; Cahn, Wiepke; de Haan, Lieuwe; Delespaul, Philippe; Luykx, Jurjen J.; Myin-Germeys, Inez; Kahn, Rene S.; et al.
Abstract: Background: Research on environmental and individual risk-factors in patients with a psychotic disorder and co-occurring obsessive-compulsive symptoms (OCS) is limited. Objective: This study aimed to examine the role of childhood trauma and coping on the occurrence of OCS in patients with a psychotic disorder and on a subclinical level in siblings. Participants and setting: 626 patients and 638 siblings from the Genetic Risk and Outcome of Psychosis (GROUP) study were included in the current study. Methods: Differences between patients and siblings with and without OCS were analyzed with between-group comparisons. Mediation analyses investigated the effect of coping on the association between trauma and OCS severity. Results: Patients and siblings with OCS reported more childhood traumatic events, particularly sexual (OR = 1.62 / 3.26) and emotional (OR = 1.47 / 2.04) abuse compared to those without OCS. Both patients (d = 0.69) and siblings (d = 0.49) with co-occurring OCS showed a higher tendency for dysfunctional passive coping strategies compared to the group without OCS. The tendency for passive coping mediated the association between sexual and emotional abuse and OCS severity in patients. Conclusions: Results imply that childhood trauma is associated with the presence of co-occurring OCS. Enhancing active coping strategies might have a beneficial effect in the prevention and treatment of co-occurring OCS in patients with psychotic disorders.